Morphoanatomical Responses and Stomatal Conductance in Shaded and Sun-Exposed Broussonetia papyrifera Seedlings - Maria Bin-i Sales Baradi; Jonathan Ogayon Hernandez (Department of Forestry, Faculty of Agriculture, University of Lampung, 2023)
Investigating invasive species’ morphoanatomical characteristics, such as leaf area and thickness of vascular tissues and storage cells, can reveal information about their adaptive ability and competitive advantage. Thus, we analyzed the variation in leaf, stem, and root morphoanatomical structure and stomatal conductance between shaded and sun-exposed seedlings of Broussonetia papyrifera to provide insights into management strategies to control its invasive ability. The variations in leaf area (LA), Leaf Mass per Area (LMA), stomatal density, thickness of palisade and spongy mesophyll tissues, thickness of xylem parenchyma cells, diameter of all xylem vessels in stem and roots and stomatal conductance were analyzed between shaded and sun-exposed seedlings. Results revealed that the LA and LMA of B. papyrifera were significantly larger in the sun-exposed than in the shaded condition. Seedlings exposed to sunlight also had thicker palisade mesophyll and xylem parenchyma cells. The diameter of xylem vessels in roots was also significantly higher in sun-exposed seedlings. Contrarily, a reverse pattern was observed in the diameter of stem xylem vessels (i.e., shaded > sun-exposed seedlings). Physiologically, a higher stomatal conductance was also observed in sun-exposed seedlings. In conclusion, we found significant variations in leaf, stem, and root morphoanatomy and stomatal conductance between shaded and sun-exposed seedlings of B. papyrifera. The findings of the present study may provide valuable implications for managing or controlling its invasibility in the introduced range. Keywords: freehand technique, invasive species, Moraceae, paper mulberry, stomatal conductance